PERANCANGAN DATABASE SISTEM INFORMASI PELAYANAN MASYARAKAT PADA KECAMATAN CADASARI KABUPATEN PANDEGLANG - Muhammad Surya Fauzan (2020)
Community services in Cadasari District are less than the performance of employees and community service users who still use conventional systems by doing them manually and data is still stored in the form of archives so that community services in Cadasari District are less than optimal. With the design of a community service information system in Cadasari District, it is quite helpful in implementing sub-district community services. The purpose of this study was to design a database which is the process of making designs that support operations and community services in Cadasari District. The use of database design in the government sector, especially in the district to store data or make changes and display the data back quickly and easily, where the public can see more transparent information. By using the Lifecycle database method which has several fairly specific database design stages. From the use of the Database Lifecycle method, it is hoped that it can help in solving community service problems in Cadasari District. The results of this research are in the form of a community service information system database design, of course with the implementation of this database design research is expected to produce a useful outcome for the service needs of Cadasari District and also the community